Recovering from a Lumpectomy or Mastectomy - Martha C. Monroe; Barbara F. Shea (EDIS)
FCS-8830, a 6-page fact sheet by M.C. Monroe and B.F. Shea, describes the recovery process for these two operations using reactions and descriptions provided by the Gainesville Breast Cancer Support Group of Florida. Published by the UF Department of Family Youth and Community Sciences, March 2009.